A proposal for a new educational model: Geoconservation Education (GEOEDU) model - Korogiu, Fatih; Mulayim, Ouz; Alkac, Onur (Keai Publishing Ltd, 2025)
The 21st century has brought with it the emergence of many new technologies. Unfortunately, many of these innovations are accompanied by negative and potentially even harmful side effects. In particular, many of these technologies are associated with the uncontrolled and irreversible destruction of natural resources as well as the disruption of education and social balance. The education system must adapt to a changing world to promote the development, protection, and awareness of global citizens as well as social justice. Within this framework, it is essential to instil the fundamental principles of common education and the desire to protect the Earth and its resources. Scientific knowledge obtained from geoscience is crucial for understanding our environment and must be used for the benefit of conserving Earth systems. This article introduces the Geoconservation Education (GEOEDU) framework, aims to propose, develop, and implement a module that is closely integrated into the educational process, and ultimately aims to demonstrate the value of its impact (c) 2025 Beijing Normal University. Publishing services by Elsevier B.V. on behalf of KeAi Communications Co. Ltd. This is an open access article under the CC BY license (http:// creativecommons.org/licenses/by/4.0/).
Keywords: educational model; geosciences; geoconservation; geoconservation education